Avenue trees of urban landscape Tiruppur City, Tamil Nadu - Prakash, Laxmanan; Ramarajan, Sekar; Manikandan, Perumal (Indian Forester, 2020)
The present study was conducted to avenue trees diversity in the 10 km radius of the Tiruppur district centre during January 2017 to December 2017. A total of 113 invasive alien plant species were recorded which belonged to 33 families and 89 genera. Among the species 92.04% were dicots, 7.08% were monocots and 0.88% were gymnosperms. Fabaceae formed the most dominant family with 28 tree species, followed by Moraceae (9 species). The species rich genera included Ficus (7 species), Terminalia, Acacia, Plumeria, Albizia and Bauhinia (3 species each). This present study revels to wealth of tree diversity of Tiruppur district centre.